Implementasi K-pop Star Pada Perancangan Interior Korean Wave Exhibition Center di Surabaya - S.P Honggowidjaja, Rebecca Chandra (Intra, 2013)
Korean wave is a music phenomenon become popular in Korea and throughout the world, including in Indonesia itself. Many of the people of Indonesia who have